Exploratory cost-effectiveness model of electromagnetic navigation bronchoscopy (ENB) compared with CT-guided biopsy (TTNA) for diagnosis of malignant indeterminate peripheral pulmonary nodules. Issue 1 (12th August 2020) - Rickets, William; Lau, Kelvin Kar Wing; Pollit, Vicki; Mealing, Stuart; Leonard, Catherine; Mallender, Philip; Chaudhari, Nilanjan; Shah, Pallav L; Naidu, Umamamaheswar Babu
Abstract : Introduction: Lung cancer is accountable for 35 000 deaths annually, and prognosis is improved when the cancer is diagnosed early. CT-guided biopsy (transthoracic needle aspiration, TTNA) and electromagnetic navigation bronchoscopy (ENB) can be used to investigate indeterminate pulmonary nodules if the patient is unfit for surgery. However, there is a paucity of clinical and health economic evidence that directly compares ENB with TTNA in this population group. This cost-effectiveness study aimed to explore potential scenarios whereby ENB may be considered cost-effective when compared with TTNA. Methods: A cohort decision analytic model was developed using a UK National Health Service perspective. ENB was assumed to have equal sensitivity to TTNA at 82%. Lifetime costs and quality-adjusted life-year (QALY) gain were calculated to estimate the net monetary benefit at a £20 000 per QALY threshold. Sensitivity analyses were used to explore scenarios where ENB could be considered a cost-effective intervention. Results: Under the assumption that ENB has equal efficacy to TTNA, ENB was found to be dominant (less costly and more effective) when compared with TTNA, due to having a reduced risk and cost of adverse events. This conclusion was most sensitive to changes in the cost of intervention, estimates of effectiveness and adverse event rates. Discussion: ENB is expected to be cost-effective when the likelihood of an accurate diagnosis is equal to (or better than) TTNA, which may occur in certain subgroups of patients in whom TTNA is unlikely to accurately diagnose malignancy or when an experienced practitioner achieves a high accuracy with ENB.